Photochemical Analysis of Food Species of the Cruciferous (Cabbage) Family - B. Ashirova, Zh.; Ð•. Anuarova, L.; Ð¢. Berik, N.; S. Newsome, A.; M. Rakhmetova, A.; Y. Yessenbekova, A.; T. Abdrasulova, Zh.; Zh. Kuzhantaeva, Zh. (International Journal of Engineering and Technology, 2018)
The article deals with several species of the cruciferous family (Cruciferae Juss.): headed cabbage (Brassica oleracea L.), turnip cabbage (BrassÑ–s rapa L.), cultivatedÂ radish (Raphanus sativus L.), horseradish (Armoraciarusticana Gaerth.-Mey-Scherb.), Italian asparagus, or broccoli (Brassica Sylvestris L., or Brassica oleracea L.), and others. It has been determined how many micro- and macroelements, as well as fat-Â or water-soluble vitamins they contain. The phytochemical research has been conducted in the Food Safety and Quality Assessment Laboratory of the Almaty Technological University. The photochemical analysis of the species concerned has been carried out in accordance with GOST 25555.3-82, GOST 30417-69, and M-04-41-2005. Â Â Â